ДВА ПІДХОДИ ДО РОЗРАХУНКУ ЕЛЕКТРОТЕПЛОВИХ ПРОЦЕСІВ ПІД ЧАС ІНДУКЦІЙНОГО НАГРІВУ РУХОМОЇ ЗАГОТОВКИ – НА ОСНОВІ ТЕОРІЇ ПОЛЯ ТА ТЕОРІЇ ТЕПЛОВИХ КІЛ - Щерба, А.А.; Подольцев, О.Д.; Кучерява, І.М.; Золотарьов, В.М.; Білянін, Р.В. (Інститут електродинаміки Національної академії наук України, 2021)
The model for the computation of thermal processes in induction heating installations with moving ingots is developed using equivalent thermal circuits. The controlled current sources as additional elements in the model are used to take into account the convective heat transfer along the moving ingot. The model is implemented in the program Matlab/Simulink and makes it possible to determine the temperature distribution along the ingot under steady-state heating conditions. The results are compared with data obtained by the alternative method which is based on the electromagnetic and thermal field theory and realized in the Comsol program. As shown the computational results by two methods concerning the temperature distribution along the ingot are in good agreement. The existing advantages and shortcomings of the used approaches are discussed. Ref. 8, fig. 3, table.